Ownership Patterns and Landscape Diversity: Conservation Implications in Maryland - Luke Macaulay; Yashwanth Reddy Pinnapu Reddy; Evan Griffiths (Land)
Land management decisions and conservation value are heavily influenced by land ownership, land cover, and land use. Our research aimed to examine ownership and land cover distribution, classify landowners based on land cover composition, and evaluate the ability of land cover clustering to be predictive of landowner motivations and behaviors in Maryland, USA. We tabulated a high-resolution land cover map against ownership boundaries, applied hierarchical clustering, and identified five landowner types characterized by a dominant land cover: (1) forest, (2) turf grass, (3) developed, (4) hay/pasture, and (5) crops. We analyzed a landowner survey of 3344 respondents to reveal how clusters predicted recreation, conservation, income, and other motivations. We found a skewed ownership distribution: 95.3% of smaller ownerships (<5 acres) cover 27.3% of the land, while 4.7% of larger owners hold 72.7%. Ownership patterns vary by cover, with forests and wetlands showing bimodal distributions, unimodal for cropland and hay/pasture, and turf grass concentrated in smaller properties. Survey analysis showed that crop, hay/pasture, and forest clusters had income percentages increasing with property size, with crop and hay/pasture accelerating more; conservation interest rose with size for forest and crop, but not hay/pasture; hunting motivation was highest in forest but increased with size similarly across clusters; non-hunting recreation motivation was highest in smaller hay/pasture properties, but decreased with size for all. Although each landowner has unique motivations and goals, our results reveal trends mediated by size of property and land cover that can be used to target outreach and improve conservation outcomes across Maryland’s diverse landscape.